Attention manipulation and information overload - Petra Persson (Research Institute of Industrial Economics (IFN), 2013)
When a decision-maker's attention is limited, her decisions depend on what she focuses on. This gives interested parties an incentive to manipulate not only the substance of communication but also the decision-maker's attention allocation. This paper models such attention manipulation. In its presence, competitive information supply can reduce the decision-maker's knowledge by causing information overload. Further, a single information provider may deliberately induce information overload to conceal information. These findings, pertinent to consumer protection, suggest a role for rules that restrict communication, mandate not only the content but also the format of disclosure, and regulate product design.
Keywords: D82; D83; D18; M38; 330; Communication; Information Overload; Limited Attention; Persuasion; Disclosure; Complexity; Consumer Protection; Salience